2016 LITHUANIAN PARLIAMENTARY ELECTIONS: IMPLICIT AND EXPLICIT ATTITUDES OF YOUNG ADULTS TOWARD THE POLITICAL PARTIES - Maceina, Tomas; Valickas, Gintautas (Politologija, 2017)
Our study is directed toward the examination of attitudinal grounds of political decision-making among young (≤ 24 years old) Lithuanian voters in the national parliamentary elections. The focus is on their attitudes regarding politically specific evaluative dimensions (competence, honesty and leadership). To estimate the prognostic values of explicit/implicit attitudes toward different Lithuanian political parties, we asked participants to fill out a questionnaire and to perform three sets of ST-IATs respectively. Due to the low voting diversity among participants, an elaborate data analysis could only be conducted regarding two Lithuanian parties: the Liberal Movement (LRLS) and Homeland Union – Lithuanian Christian Democrats (TS-LKD). The results of our study suggest that explicit attitudes are more important than implicit attitudes in predicting voting behavior. We found that positive explicit and positive implicit attitudes toward the LRLS competence and leadership, respectively, predicted the decision to vote for this party (reference group: non-voters). On the same note, our findings suggest that positive explicit and implicit attitudes toward the TS-LKD honesty predicted the decision to vote for this party (reference group: non-voters). Positive implicit attitudes toward the party’s competence also predicted this decision. Finally, we found that political sophistication was an important factor by only considering explicit attitudes toward TS-LKD. Namely, the increase of explicit attitudes’ prognostic power on the decision to vote for TS-LKD was associated with the decrease of voters’ political sophistication (reference group: non-voters).